THE READINESS OF ELEMENTARY SCHOOL STUDENTS TO FACE MENARCHE: LITERATURE REVIEW - Putri Via; Neni Nuraeni; Ida Rosidawati (Journal of Maternity Care and Reproductive Health, 2021)
Menarche is the first menstruation for a woman as a sign that the fertile cycle has begun. The negative impact will happened when the child experiences menarche such as; anxious, afraid of shock and restless. The purpose of this Literature Review is to know the readiness of elementary school students to face menarche. This research method is literature review by using Google Scholars Search Engine and Garuda Portal obtained 13 articles that match the keyword readiness of menarche.  The results showed that age and knowledge about menarche greatly influenced by the readiness of children to face menarche. The readiness of younger child experiences menarche is very limited so that the child will feel anxious, afraid, shocked and restless. It is recommended to maximize the role of the family in providing information about menarche to the child.